2003
DOI: 10.1073/pnas.0835166100
|View full text |Cite
|
Sign up to set email alerts
|

Endonuclease cleavage of blocked replication forks: An indirect pathway of DNA damage from antitumor drug–topoisomerase complexes

Abstract: The cytotoxicity of several important antitumor drugs depends on formation of the covalent topoisomerase-DNA cleavage complex. However, cellular processes such as DNA replication are necessary to convert the cleavage complex into a cytotoxic lesion, but the molecular mechanism of this conversion and the precise nature of the cytotoxic lesion are unknown. Using a bacteriophage T4 model system, we have previously shown that antitumor drug-induced cleavage complexes block replication forks in vivo. In this report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…Replication fork blockage can allow a branch-specific endonuclease to cleave one arm of a fork (30,42), and then two general models for RC replication are possible. In one model, RC replication ensues after gap repair/ligation at the broken fork and replication restart at the unbroken fork ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Replication fork blockage can allow a branch-specific endonuclease to cleave one arm of a fork (30,42), and then two general models for RC replication are possible. In one model, RC replication ensues after gap repair/ligation at the broken fork and replication restart at the unbroken fork ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, topo II poison-induced cleavable complexes have been shown to be proteolytically degraded by the ubiquitin/26 S proteasome pathway, and a model is suggested in which the repair of cleavable complexes may involve transcription-dependent topo II proteolysis to reveal the protein-concealed DSBs (41). It is also suggested that the collision of DNA replication machinery with cleavable complexes leads to generation of overt DSBs (42). Such protein-free DSBs would then be repaired by the DSB repair pathway(s).…”
mentioning
confidence: 99%
“…This decrease is consistent with EndoVII-mediated cleavage of the regressed fork Holliday junction. However, previous reports have suggested that EndoVII also cleaves Y-shaped molecules, such as the origin fork, in vivo (14,15). Direct cleavage of the origin fork junction by EndoVII would decrease the number of origin forks available for regression, indirectly decreasing the accumulation of regressed origin forks.…”
Section: Accumulation and Resolution Of Origin Forks In Various Mutantmentioning
confidence: 96%
“…Several reports have described the appearance of DSEs (and/or broken chromosomes) in association with replication fork stalling (15,(25)(26)(27)(28). DSEs could be created from stalled forks by several possible mechanisms, including fork breakage during inactivation, fork cleavage by endonucleases, head-to-tail fork collisions, and fork regression.…”
Section: T4 Origins Provide a Model For Stalled Fork Processingmentioning
confidence: 99%
See 1 more Smart Citation